PEMILIHAN PERANGKAT LUNAK PEMINDAHAN BERKAS DALAM MENINGKATKAN PEMANFAATAN TELEPON PINTAR - Redaksi Tim Jurnal (KILAT, 2018)
Data processing technology services, smart phone technology and information communication technology can be applied without the use of cables. By utilizing wireless communication services, it will minimize cable usage. The problem faced by users is how to determine the type of wireless communication services installed on data processing technology devices, smart phone technology and information communication technology based on predetermined criteria. The purpose of this research is expected to determine the type of wireless communications services installed based on the criteria specified. This research problem can be solved by using multi-criteria decision making and analytical hierarchy process approach. This approach was chosenbecause the approach was able to choose the best alternative from several alternatives to solve the problem of choosing the type of wireless communication service. The result of data processing chooses share-it 43.3%, super-beam 30.5%, and fast file transfer 26.3%. The data inconsistency rate is considered good because it is 0.01, smaller than 0.1 as the maximum value of the inconsistency ratio.